Lemons to Lemonade: Educational Modifications During the COVID-19 Pandemic and their Utility Moving Forward - Ellis S. Logan; Brandon Atkins; Anne M. Price (Journal of Public and Professional Sociology, 2024)
The COVID-19 pandemic necessitated changes across social institutions, including education. This case study outlines specific innovations using five cases of pedagogical developments made by social science faculty members at a public university, and their utility for undergraduate students in a post-pandemic world. These innovations relate specifically to office hour scheduling, class assignment reminders, building informal class support groups, experiential learning, and virtual paper submission and evaluation. For each case, we outline the implementation procedure, evaluate its effectiveness, and discuss the benefits. We argue that these methods, forged during “challenging times”, will help improve students’ experiences and success during their time in college, and benefit instructors in higher education in a variety of ways.